Análisis de los costos de inversión y su incidencia en el financiemiento para la siembra de 74 hectareas de cacao CCN-51 en la finca Rio Lindo bajo de la empresa Agrotropical S.A. en el cantón Quevedo, período 2009. - Godoy Espinoza, Martha Piedad (2010)
The economy in Ecuador has been strongly linked to the production of cocoa, (Teobroma Cacao L.) from the colonial period and during the Republic. This culture is linked to historical, economic, political and social life of Ecuador. Cocoa production has traditionally been much of the country agricultural area the Andean sub-region, mobilizing tens of thousands of laborers and farm families along the coast, also attracting labor from the sierra region. Its production during this century has been one of the main items of the Ecuadorian Agricultural Sector, at least until the banana boom will start in 1969 and the tanker in 1972, generating resources and jobs, plus a large supply of foreign exchange through exports, a situation which allowed us to contribute to the development and progress of the Ecuadorian economy, especially in the beginning of this century. Ecuador a country with great tradition in cococa production worldwide, becoming the largest exporter in the early twentieth century, has a great tradition as a producer and exporter, the contry economic history is linked to this product; during the last years has strongly encouraged the plating of cocoa tech variety CCN-51 clone the many benefits it offers the same in yield figure as disease resistance. With the analysis in this research, we found that cocoa-plating project with the variety CCN-51 is feasible as we did ten years projections with reference to an interest rate of 12% applied to capital and an opportunity rate of 10%, which gives results in a positive net present value of $. 1,036.181.02; the initial investment amounts to $. 446.480.00 which includes crop establishment more fixed investment, they are recovered over a period of 3.35 year. It should be noted that performing the analysis of the internal rate of it resulted en 14.31%, being higher than the rate of 3.64 % applied to the project opportunity, which indicates that it is profitable. ...................................